2012
DOI: 10.1002/jctb.3718
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a gaseous mixture by biofilters filled with an inorganic packing material: performance and influence of inoculation on removal efficiency levels

Abstract: BACKGROUND: The impact of inoculation on performance and subsequent community structure is a critical question in gas biofiltration processes. Thus, the aim of this study is to evaluate the impact of inoculation on biofilters packed with an inorganic medium and fed with a gaseous mixture (oxygenated and sulphur compounds).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…() and Gadal‐Mawart et al . () did investigate biodegradation efficiencies in biofilters. Due to the environmental conditions in the top layer of these biofilter columns (low humidity and high toxic pollutant concentrations), most compounds were eliminated in the middle and lower parts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() and Gadal‐Mawart et al . () did investigate biodegradation efficiencies in biofilters. Due to the environmental conditions in the top layer of these biofilter columns (low humidity and high toxic pollutant concentrations), most compounds were eliminated in the middle and lower parts.…”
Section: Discussionmentioning
confidence: 99%
“…; Gadal‐Mawart et al . ). A number of abiotic factors could be important for determining differences in pesticide degradation rate throughout the BPS matrix.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result can be explained by low selective pressure (concentration of contaminants) and high resource availability (biodegradable compounds, nutrients) in BF1 and BF2, which influence the community composition. This may be an indication of functional redundancy, which is ensured by the presence of a reservoir of species able to perform the same ecological function . Then, targeting the total bacterial community, with current 16S rDNA‐based methods, may not be discriminant enough to reveal the potential link between a characteristic of the packing material, the removal performances and the local development of adapted populations.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that it is possible to find radial gradients in the microbial population due to heterogeneities in the packing material, that may result from the occurrence of preferential pathways, different pollutants and nutrients concentration, etc. (Gadal-Mawart et al, 2011).…”
Section: Resultsmentioning
confidence: 99%